Reduced lifespan of erythrocytes in Dahl/Salt sensitive rats is the cause of the renal proximal tubule damage - Eri Manabe (Nature Portfolio, 2020)
Abstract We studied the mechanisms of anemia and the influence of anemia on renal pathology in Dahl/Salt Sensitive (Dahl/SS) rat, a model of cardio-renal-anemia syndrome. Erythrocyte lifespan was shortened and associated with decreased hemoglobin level in the Dahl/SS rats given high-salt diet. Serum haptoglobin decreased, reticulocytes increased, and erythropoiesis in the bone marrow and extramedullary hematopoiesis in the spleen was markedly stimulated by increased serum erythropoietin in them. As a mechanism of hemolysis, we investigated the incidence of eryptosis, suicidal death of erythrocytes. Eryptosis was increased, and red blood cell-derived microparticles, small particle which are generated in hemolytic disease, were also increased in Dahl/SS rats fed with high-salt diet. Deposition of hemosiderin and mitochondrial morphologic abnormality, a sign of ferroptosis, in proximal renal tubules was associated with intravascular hemolysis. Treatment with deferasirox, an oral iron chelator, reduced the renal proximal tubular injury and the glomerular sclerosis in Dahl/SS rats fed with high-salt diet. In conclusion, reduced half-life of erythrocytes induced by hemolysis is the major cause of anemia in Dahl/SS rat. Iron accumulation induced by hemolysis causes renal proximal tubule injury and accelerates renal damage in this model.